All your perfects : a novel - Hoover, Colleen (New York : Atria Books, 2018)
A damaged couple in a troubled marriage grapple with the memories and mistakes they've made and secrets they've kept as they try to repair their love.
Keywords: Marriage -- Fiction; Married people -- Fiction; Man-woman relationships -- Fiction; Infertility -- Fiction; Romance fiction; Psychological fiction